Borderline personality disorder, therapeutic privilege, integrated care: is it ethical to withhold a psychiatric diagnosis? - Sims, Erika (Journal of medical ethics, 2022)
Once common, therapeutic privilege—the practice whereby a physician withholds diagnostic or prognostic information from a patient intending to protect the patient—is now generally seen as unethical. However, instances of therapeutic privilege are common in some areas of clinical psychiatry. We describe therapeutic privilege in the context of borderline personality disorder, discuss the implications of diagnostic non-disclosure on integrated care and offer recommendations to promote diagnostic disclosure for this patient population.